Indirect Detection of Burkholderia pseudomallei Infection in a US Marine After Training in Australia. (23rd March 2020) - Larson, Derek T; Schully, Kevin L; Spall, Ammarah; Lawler, James V; Maves, Ryan C
Abstract: In 2012, the United States Marine Corps began annual deployments around Australia, including highly endemic areas for Burkholderia pseudomallei . B. pseudomallei infection, or melioidosis, is difficult to diagnose, and culture remains the gold standard. Accurate and timely diagnosis is essential, however, to ensuring appropriate therapy. Ten days after returning from Australia, a Marine presented to a community hospital with massive cervical lymphadenopathy, fever, and cough. Computed tomography demonstrated scattered pulmonary infiltrates with small cavitations; lymphadenopathy involving the cervical, supraclavicular, and mediastinal nodes; and splenomegaly. Sputum and blood cultures were negative. Empiric antimicrobial therapy with ceftazidime was initiated for suspected melioidosis. Retrospectively, a prototype iSTAT cartridge modified to detect B. pseudomallei capsular polysaccharide antigen was used to test a specimen of the patient's blood and was determined to be positive. Over the course of therapy, B. pseudomallei capsular antigen levels in blood declined as the patient improved. The leveraging of an existing point-of-care (POC) analyzer to create a rapid diagnostic assay for melioidosis provides a template for rapid POC diagnostics that could significantly improve the ability of clinicians to deliver timely and appropriate therapy for serious infections.